Role of grain boundary engineered microstructure on high temperature steam oxidation behaviour of Ni based superalloy alloy 617 - Athreya, C. N.; Deepak, K.; Kim, Dong-Ik; de Boer, B.; Mandal, Sumantra; Sarma, V. Subramanya (ELSEVIER SCIENCE SA, 2019)
The effect of grain boundary engineered microstructure on isothermal and cyclic high temperature oxidation of Ni based alloy 617 in steam comprising of 20% H2O vapour is studied. The grain boundary character and network in alloy 617 was modified through thermomechanical processing by subjecting material to cold rolling and annealing. The isothermal oxidation resistance improved significantly after the thermomechanical processing and is attributed to the increase in twin boundary fraction and disruption of random high angle grain boundary network. Weight loss due to spallation and volatilization of chromium oxide is observed in the thermo-mechanically processed specimen during cyclic oxidation. It is attributed to reduction in grain size and non-uniform grain size distribution following thermomechanical processing. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: DEGREES-C; WATER-VAPOR; CORROSION; KINETICS; METALS; STEEL; SIZE; 800H